Нові відомості про поширення Nectria nigrescens Cooke в Україні - Довбня, М.О.; Кузнєцов, М.О.; Суздальцев, М.Ю. (Київ : Інститут ботаніки ім. М.Г. Холодного НАН України, 2021)
New data about the registration of Nectria nigrescens Cooke on the territory of Ukraine, confirmed by its ITS region sequence, are presented.
Dovbnia M.O., Kuznietsov M.O., Suzdaltsev M.Yu. New data about the distribution of Nectria nigrescens Cooke in Ukraine
Keywords: fungi; biodiversity; new records; Ukraine